Between-season attraction of cotton boll weevil, Anthonomus grandis Boh. (Coleoptera: Curculionidae) adults by its aggregation pheromone - Wedson Desidério Fernandes; Sérgio Luis de Carvalho; Mohamed Habib (Scientia Agricola, 2001)
The present study was undertaken to investigate the attractiveness of boll weevil adults by its aggregation pheromone under winter field conditions. Two experimental fields were utilized at "Casa Branca", SP, Brazil. For each one, three areas were established near the refuge vegetation, sparated 500 m from each other. Each area was divided in three sub-areas or blocks of 100 m² to receive pheromone applications (2.5 g per block). In addition to the pre-application counting, five additional evaluations were carried out after the pheromone applicaton. Ten randomized sampling points per block were considered in each evaluation process. A. grandis adults responded immediately to the pheromone applications, and were captured for 14 days . The highest level of attractiveness was observed 24 hours after application. The application of the boll weevil aggregation pheromone during winter could increase the predation by natural enemies, due to the increase of prey availability. Chemical control can be recommended 24 hours after pheromone applications in small plots as a between-season strategy for the suppression of boll weevil adults.